Association between triglyceride-glucose index and 6-month readmission in patients with heart failure: a cohort study - Li, Huibo; Jiang, Yujie; Zheng, Dong; Lin, Guixiong; Feng, Yanling; Zhuo, Yufeng; Zhang, Peng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundInsulin resistance (IR) significantly impacts outcomes in heart failure (HF) patients, by the triglyceride-glucose (TyG) index serving as an effective marker of metabolic dysfunction. However, its association with HF readmission risk is still uncertain.MethodsThis study analyzed 901 HF patients using multivariable logistic regression and restricted cubic splines to evaluate the relationship between the TyG index and 6-month readmission risk.ResultsPatients in the lowest TyG quartile (Q1) had a significantly higher risk of 6-month readmission across models: Model 1 [odds ratio (OR) 1.72, 95% confidence interval [(CI) 1.16–2.53; p = 0.007], Model 2 (OR 1.83, 95% CI 1.23–2.72; p = 0.003), and Model 3 (OR 1.71, 95% CI 1.12–2.61; p = 0.012). A nonlinear relationship between the TyG index and the 6-month readmission risk was observed (p for nonlinearity = 0.046). Furthermore, significant interactions were detected between the TyG index and body mass index (BMI) subgroups (p for interaction = 0.002). Including the TyG index modestly improved predictive performance, particularly in abnormal BMI patients.ConclusionA nonlinear relationship between the TyG index and 6-month readmission risk in HF patients. Subgroup analyses revealed that a lower TyG index was significantly connected to a higher readmission risk, especially in patients with abnormal BMI. Although the TyG index improved predictive performance, its overall discriminative ability remained modest, demonstrating greater utility in populations with abnormal BMI.